2009
DOI: 10.1007/s12596-009-0013-x
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and performance-analysis of a planar silica-based cascaded symmetric Y-branch 1 × 8 optical power splitter

Abstract: Fabrication of a planar silica-based cascaded symmetric Y-branch 1 8 optical power splitter is described in this study. Post-fabrication, thorough analysis of device-performance is presented in terms of insertion loss, nonuniformity and polarization-dependent loss. The fabricated device is designed based on cascaded Y-branching waveguide, comprising of a linear taper and symmetric S-bend arc branching waveguides. The simulated values of the average insertion loss, non-uniformity and polarization-dependent loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…However, after characterization of the device, the post-fabrication characterization of the device shows a poor performance [8], when tested over the full C+L band wavelength region in the optical window. This is due to major limitations towards the achievement of a perfect Y-junction with almost zero-gap splitting zone in silica-on-silicon technology, during fabrication through some critical processes like photolithography, reactive ion etching and plasma enhanced chemical vapour deposition (PECVD).…”
Section: Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, after characterization of the device, the post-fabrication characterization of the device shows a poor performance [8], when tested over the full C+L band wavelength region in the optical window. This is due to major limitations towards the achievement of a perfect Y-junction with almost zero-gap splitting zone in silica-on-silicon technology, during fabrication through some critical processes like photolithography, reactive ion etching and plasma enhanced chemical vapour deposition (PECVD).…”
Section: Limitationmentioning
confidence: 99%
“…Various research groups have designed, fabricated and demonstrated several techniques like Y-branch splitter [1][2][3][4][5][6][7][8], multimode interference based splitter [9], directly UVwritten optical splitter [10] and so on, for achieving a compact, low-loss and cost-effective optical splitter. Among 1 3 these, Y-branch optical splitter is much popular because of its design simplicity, where the basic unit of this 1×N optical splitter is the Y-branch 1×2 optical power splitter.…”
Section: Introductionmentioning
confidence: 99%
“…Assembling these devices presents unique requirements and challenges [1][2][3]. Assembling these devices requires aligning dozens, even hundreds of channels of planar optical waveguide, with a cross section of 4µm × 4µm to 8µm × 8µm, to SMFs with a core diameter of 8~9µm [4,5]. The most common method uses optical fiber array to attach optical fibers to multi-channel optical waveguide chips as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%